Optimal Trade and Industrial Policy under Oligopoly - Eaton, Jonathan; Grossman, Gene M. (Quarterly Journal of Economics, 1986)
In this paper we provide an integrative treatment of the welfare effects of trade and industrial policy under oligopoly, and characterize qualitatively the form that optimal intervention takes under a variety of assumptions about the number of firms, their conjectures about the response of their rivals to their actions, the substitutability of their productsand the markets in which they are sold. We find that when no domestic consumption occurs optimal policy under duopoly with a single home firm depends on the difference between firms' actual responses to their rivals and the response that their rivals' conjecture. If conjectures are consistent , free trade is optimal. A tax or subsidy is indicated depending on the sign of the difference between the conjectured and the actual reponse.With more than one home firm but still no domestic consumption, an export tax is indicated if conjectures are consistent. Production subsidies and export tax-cum-subsidies can raise national welfare in the presence of domestic consumption, because these policies can mitigate the extent of the consumption distortion implicit in the deviation of price from marginal cost.